A Survey of Computerization of Selected Community Pharmacies in Southwestern Nigeria (Nigerian Journal of Pharmaceutical Research, 2020)
Background: The use of computers has had impact in all professions including pharmacy. Computers have found lots of application in the management of inventories, electronic prescribing and counting machines for tablets and capsules.Objective: This research was designed to identify the types of technology devices and programs in use by community pharmacies, capabilities of software in use, as well as to identify the challenges faced by community pharmacists in the use of computerized systems in their premises.Method: A cross-sectional survey of 217 community pharmacies in 6 Southwestern Nigerian states was done using a set of questionnaires. Data gathered was subjected to statistical analysis using SPSS version 17.Results: Some community pharmacies in Southwestern Nigeria used inventory management software (47.0%). The reported capabilities of the software packages in use included sales processing (99.0%), account processing (88.2%) and POS link (62.7%). The reasons why some community pharmacies have not computerized their outlets were erratic power supply (56.2%), high cost of the devices (48.4%) and low turnover (35.9%). The major challenges faced by community pharmacists in the use of computer devices in their premises included erratic power supply (90.2%) and high cost of fuel (83.3%).Conclusion: The level of computerization of community pharmacies in Southwestern Nigeria was observed to be generally low. Erratic power supply and cost of device were major challenges to the computerization of community pharmacies in Southwestern Nigeria
Keywords: Community Pharmacy; Software; Computerization